Neuronal polarization in the developing cerebral cortex - Sakakibara, Akira; Hatanaka, Yumiko (Frontiers in Neuroscience, 2015)
Cortical neurons consist of excitatory projection neurons and inhibitory GABAergic interneurons, whose connections construct highly organized neuronal circuits that control higher order information processing. Recent progress in live imaging has allowed us to examine how these neurons differentiate during development in vivo or in in vivo-like conditions. These analyses have revealed how the initial steps of polarization, in which neurons establish an axon, occur. Interestingly, both excitatory and inhibitory cortical neurons establish neuronal polarity de novo by undergoing a multipolar stage reminiscent of the manner in which polarity formation occurs in hippocampal neurons in dissociated culture. In this review, we focus on polarity formation in cortical neurons and describe their typical morphology and dynamic behavior during the polarization period. We also discuss cellular and molecular mechanisms underlying polarization, with reference to polarity formation in dissociated hippocampal neurons in vitro.